Instalación de un sistema de riego por aspersión para 88 ha de banano (Musa paradisiaca) en Finca Monte Blanco, San Alberto, Siquirres, Limón - Salmerón-Brenes, Mariela (Instituto Tecnológico de Costa Rica, 2018)
The present Final Graduation Work was carried out in the province of Limón, specifically in San Alberto de Siquirres, in the Monte Blanco banana plantation, which belongs to the group of independent producers San Alberto S.A The project involves the installation of a sprinkler irrigation system on 88 hectares of the aforementioned farm, in order to improve and increase the production of the fruit First the farm and the installation plan were recognized, it had to start with the supervision of the trench system, which complied with the correct requirements and dimensions After that, the ditch system was already in place and began with the installation of the piping system that makes up the design, according to plans and management of the work area In the field, decisions had to be made to make modifications to the design, in order to eliminate some failure when the irrigation system was commissioned The management and coordination of the space to work and move the materials, was extremely important, due to the use of the cables via, where the fruit is transported.
Proyecto de Graduación (Licenciatura en Ingeniería Agrícola) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Agrícola, 2018.
Keywords: Sistemas de riego; Riego por aspersión; Producción; Zanjas; Tuberías